1999
DOI: 10.1161/01.res.85.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction of Rat Aortic Vascular Smooth Muscle Cells Requires RhoA and Intact Actin Filaments

Abstract: The growth-promoting effect of mechanical stress on vascular smooth muscle cells (VSMCs) has been implicated in the progress of vascular disease in hypertension. Extracellular signal-regulated kinases (ERKs) have been implicated in cellular responses, such as vascular remodeling, induced by mechanical stretch. However, it remains to be determined how mechanical stretch activates ERKs. The cytoskeleton seems the most likely candidate for force transmission into the interior of the cell. Therefore, we examined (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
147
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(160 citation statements)
references
References 41 publications
(35 reference statements)
9
147
2
1
Order By: Relevance
“…These effects are similar to those produced by latrunculin B and likely reflect the role of RhoA in regulating actin cytoskeletal assembly (13). Activation of RhoA by stretch has been demonstrated in cultured cells (26) but, to our knowledge, not in intact vascular tissue. In the present experiments C2-C3 toxin had no effect on weight or protein synthesis in unloaded tissue, whereas the growth responses to load during culture were inhibited.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…These effects are similar to those produced by latrunculin B and likely reflect the role of RhoA in regulating actin cytoskeletal assembly (13). Activation of RhoA by stretch has been demonstrated in cultured cells (26) but, to our knowledge, not in intact vascular tissue. In the present experiments C2-C3 toxin had no effect on weight or protein synthesis in unloaded tissue, whereas the growth responses to load during culture were inhibited.…”
Section: Discussionsupporting
confidence: 58%
“…Lack of effect of Y-27632 on ERK1/2 activation was also found in pressurized mesenteric arteries by Matrougui et al (24), whereas activation was inhibited in aortic cells exposed to cyclic strain as described by Numaguchi et al (26). Mack et al (18) found decreased ␣-actin promoter activity and SM22 synthesis in cultured vascular cells exposed to Y-27632.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Focal adhesions act as a bridge to link integrin cytoplasmic domain to the cytoskeleton and activate integrin-associated signaling pathways, such as the mitogen-activated protein kinase (MAPK) pathway (17) and the Rho pathway (18,19). Rho and its downstream target Rho kinase/Rho-associated coiled-coil-containing protein kinase (ROCK) (20) are involved in the reorganization of cytoskeletal components (21,22) as well as cell cycle progression (1,23, 24). Integrin-dependent adhesion can also trigger ligand-independent epidermal growth factor receptor (EGFR) activation to transduce downstream signaling (25).…”
mentioning
confidence: 99%
“…There is a large body of evidence showing that extracellular signal-regulated kinase 1/2 (ERK1/2) 1 controls cell proliferation in various cell types, including osteoblasts (5). Recent reports demonstrated that mechanical strain is able to activate ERK1/2 in several adherent cells such as mesangial cells (6), smooth muscle cells (7), and chondrocytes (8). In osteoblasts, ERK activation was mostly reported in fluid flow (9 -12), centrifugation (13), or magnetic drag force (14) experiments and in only one study using cyclic stretch (albeit combined with fluid flow) (15).…”
mentioning
confidence: 99%